Desenvolvimento de uma ferramenta de suporte à gestão de carreiras em Engenharia do Software numa empresa - Daniel Filipe Silva Ermida Martins de Freitas (2014)
The topic discussed in this thesis is the carreer management in software engineering, covering it with companies that are dedicated to software development. The thesis is developed with Critical Manufacturing and the main goal is to analyze, describe and interpret the model of carreer management that is used in CMF,allowing the implementation of improvements related to found failures. This paper discusses available models of carreer management and their application in order to create a knowledge base to better analyse Critical Manufacturing as case study. This issue emerges in a different labor context that is the software development companies market. Contrary to presented in many sectors, the work here isn't declining and unemployment is not a scourge. Rather the market is competitive and is full of great opportunities. Thus, it is necessary to reevaluate the carreer management systems in CMF in order to realize their perspective on the set of employees and how to manage their carreers in the most fair, simple and efficient possible way. Only in this way can distinguish the best and retain them in the company borders, avoiding wasting precious assets for competition. Alongside this study and review, the most effective model will be implemented with the development of a new platform to support this implementation an subsequent carreer management in Critical Manufacturing.